Histopathological analysis of central nervous system tumor; an observational study - Kakshapati, Trishna; Basnet, Ranga Bahadur; Pant, Basant; Gautam, Deepti (Journal of Pathology of Nepal, 2018)
Background: Though the central nervous system tumor comprises 2% of all the tumors, an overall increase has been observed especially in less developed countries. This increase in the incidence may be due to exposure of population to various risk factors or improved diagnosis with advancement in the ancillary studies. This study aims to provide a single centre histopathological spectrum of this type of tumor. Materials and Methods: A retrospective cross sectional study on a series of cases was performed in the Department of Pathology, Annapurna Neurological Institute & Allied Science , Maitighar , Kathmandu, Nepal from April 2013 to Jan 2016. Data were analyzed using SPSS version 21.0. Results: A total of 221 brain and CNS tumors (125 females and 96 males) were studied. The mean age at diagnosis was 43.77 years. The most common tumor was meningioma(67 cases, 30.3%), followed by astrocytic tumor (57 cases, 25.7%) and pituitary adenoma(30 cases,13.6%). The frequency of WHO grade I, II,III and IV tumor were 94 cases (55%), 34 cases (19.9%),10 cases (5.8%), and 33 cases (19.3%) respectively. The astrocytic tumor was most frequent tumor in children (7/20 caes, 37 %). Conclusion: This study showed the most common CNS tumor to be meningioma followed by astrocytic tumors and pituitary adenoma. The spectrum of CNS tumor in children showed divergent histologic pattern according to the age. In age group 0-10 years embryonal tumors were common whereas ages group of 12-years showed propensity towards astrocytoma as in adults.